Economic impact of surgery on households and individuals in low income countries: A systematic review. (June 2021) - Platt, Esther; Doe, Matthew; Kim, Na Eun; Chirengendure, Bright; Musonda, Patrick; Kaja, Simba; Grimes, Caris E.
Abstract: Background: Surgical disease in Low Income Countries (LIC) is common, and overall provision of surgical care is poor. A key component of surgical health systems as part of universal health coverage (UHC) is financial risk protection (FRP) – the need to protect individuals from financial hardship due to accessing healthcare. We performed a systematic review to amalgamate current understanding of the economic impact of surgery on the individual and household. Our study was registered on Research registry (www.researchregistry.com ). Methods: We searched Pubmed and Medline for articles addressing economic aspects of surgical disease/care in low income countries. Data analysis was descriptive in light of a wide range of methodologies and reporting measures. Quality assessment and risk of bias analysis was performed using study design specific Joanna-Briggs Institute checklists. This study has been reported in line with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and AMSTAR (Assessing the methodological quality of systematic reviews) Guidelines. Results: 31 full text papers were identified for inclusion; 22 descriptive cross-sectional studies, 4 qualitative studies and 5 economic analysis studies of varying quality. Direct medical, direct non-medical and indirect costs were variably reported but were substantial, resulting in catastrophic expenditure. Costs had far reaching economic impacts on individuals and households, who used entire savings, took out loans, reduced essential expenditure and removed children from school to meet costs. Conclusion: Seeking healthcare for surgical disease is economically devastating for individuals and households in LICs. Policies directed at strengthening surgical health systems must seek ways to reduce financial hardship on individuals and households from both direct and indirect costs and these should be monitored and measured using defined instruments from the patient perspective. Highlights: The financial impact of surgery on patients and families in Low income cuntries is not well understood. We found significant impact from direct and indirect costs, both short and long-term. Our data demonstrates this for a wide variety of different surgical conditions. Global and national policies need to address financial hardship. Standard tools for measurement of this are required to monitor impact of policy.